(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Teaching English as a Second Language (ESL) involves numerous challenges that affect both teachers and students. These include language barriers, lack of motivation, differences in learning styles, and limited access to resources. Many students struggle with pronunciation, grammar, and vocabulary retention, while teachers face difficulties in maintaining student engagement